Early Infant Feeding Practices as Possible Risk Factors for Immunoglobulin E-Mediated Food Allergies in Kuwait - Dalal Alkazemi; Munirah Albeajan; Stan Kubow (International Journal of Pediatrics)
Objective. Early feeding and infant exposures have been suggested as potential risk factors for immunoglobulin E- (IgE-) mediated food allergy (FA). We aimed to evaluate the association between IgE-mediated FA in children and early exposures including the child’s nutritional status, breastfeeding and its duration, the age at which the solid food was first introduced, antibiotic exposure during the first year of life, and the child’s vitamin D status during infancy. Design. A case-control study. Setting and Subjects. Children aged 0–13 years were recruited from pediatric allergy and immunology clinics (PAICs) located at major government hospitals in Kuwait (total FA cases: n=100; boys = 67%), and healthy controls (n=100, boys 55%) were recruited from various vaccination units at primary healthcare centers. Results. Cow’s milk allergy was the most common type of FA. FA status was independently associated with the early exposures of exclusive breastfeeding (aOR = 15.55 (3.26–74.19), p=0.001), vitamin D deficiency or insufficiency during infancy (aOR = 5.42 (1.92–15.30), p=0.001), and antibiotic exposure during the first year of life (aOR = 5.00 (1.58–15.84), p=0.006). Conclusions. FA is highly prevalent among children in Kuwait, and our data indicate that early nutrition-related and antibiotic exposures are associated with FA risk.